Indigo Carmine: Between Necessity and Concern - Madalina-Elena Ristea; Otilia Zarnescu (MDPI AG, 2023)
Dyes, such as indigo carmine, have become indispensable to modern life, being widely used in the food, textile, pharmaceutical, medicine, and cosmetic industry. Although indigo carmine is considered toxic and has many adverse effects, it is found in many foods, and the maximum permitted level is 500 mg/kg. Indigo carmine is one of the most used dyes in the textile industry, especially for dyeing denim, and it is also used in medicine due to its impressive applicability in diagnostic methods and surgical procedures, such as in gynecological and urological surgeries and microsurgery. It is reported that indigo carmine is toxic for humans and can cause various pathologies, such as hypertension, hypotension, skin irritations, or gastrointestinal disorders. In this review, we discuss the structure and properties of indigo carmine; its use in various industries and medicine; the adverse effects of its ingestion, injection, or skin contact; the effects on environmental pollution; and its toxicity testing. For this review, 147 studies were considered relevant. Most of the cited articles were those about environmental pollution with indigo carmine (51), uses of indigo carmine in medicine (45), and indigo carmine as a food additive (17).